Analysis of Biological Textbooks at The High School Level on Cell Material in Second Grade (XI Class): In The Perspective of Figural Representation Aspect - Azra Khairunnisa; Rasyidah Rasyidah (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
This research aims to determine the relationship between image representation and the content of the material as well as the relationship between image representation and the reality of the image contained in the cell material. This research uses a method, namely: content analysis. Content analysis focuses on the characteristics of the material. This means that research methods are applied to written or visual material to identify certain parts of that material. The material analyzed can be textbooks, newspapers, web pages, speeches, television programs, advertisements, musical compositions, or documentation (Ary, 2010). Based on the results and discussions carried out, it can be concluded that the image representation in book A is superior compared to book B because the presentation of the images in book A is more balanced between the images, namely around discussion of cells in the material accompanied by images